2018
DOI: 10.1101/465732
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Telomere length, arsenic exposure and risk of basal cell carcinoma of skin

Abstract: Telomere length per se a heritable trait has been reported to be associated with different diseases including cancers. In this study based on arsenic exposed 528 cases with basal cell carcinoma of skin (BCC) and 533 healthy controls, we observed a statistically significant association between decreased telomere length and increased BCC risk (OR = 5.92, 95% CI = 3.92-9.01, P<0.0001). We also observed that higher arsenic exposure (>1.32 µg/L) was statistically significantly associated with decreased telomere len… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 52 publications
0
1
0
Order By: Relevance
“…However, it was suggested that women exposed to arsenic in the air with co-exposure to sunlight at work might be more susceptible to NMSC than those who are not exposed to the sun. In another multi-center case-control study, Srinivas et al (78) observed that contrary to consistent reports about the association between increased telomere length and rising incidence risk of different cancers, among people exposed to arsenic, short telomeres are correlated with increased risk of BCC. Data analysis also showed that arsenic exposure could regulate the direction of the telomere length effect.…”
Section: Long-term Chemical Exposurementioning
confidence: 78%
“…However, it was suggested that women exposed to arsenic in the air with co-exposure to sunlight at work might be more susceptible to NMSC than those who are not exposed to the sun. In another multi-center case-control study, Srinivas et al (78) observed that contrary to consistent reports about the association between increased telomere length and rising incidence risk of different cancers, among people exposed to arsenic, short telomeres are correlated with increased risk of BCC. Data analysis also showed that arsenic exposure could regulate the direction of the telomere length effect.…”
Section: Long-term Chemical Exposurementioning
confidence: 78%
“…In one study, it was reported that short telomere length increased the risk of developing colorectal cancer 20 , in another study, short telomere length was associated with an increased risk of cervical cancer in HPV-positive women 21 , and another study, short telomere length was associated with an increased risk of basal cell carcinoma of the skin in arsenic exposure. 22 In contrast to these studies, there are two different studies indicating that long telomere length is associated with an increased risk of soft tissue sarcoma, and similarly, long telomere length is associated with an increased risk of developing breast and pancreatic cancer. [23][24] It has been reported that long telomere length is associated with poor survival in breast cancer and renal cell carcinoma and may be a poor prognostic factor.…”
Section: Discussionmentioning
confidence: 99%